MicroRNAs in Papillary Thyroid Cancer: What Is New in Diagnosis and Treatment - Papaioannou, Maria; Chorti, Angeliki G.; Chatzikyriakidou, Anthoula; Giannoulis, Kleanthis; Bakkar, Sohail; Papavramidis, Theodosios S. (Frontiers in Oncology, 2022)
Introduction: Papillary thyroid cancer (PTC) accounts for up to 80% of thyroid malignancies. New diagnostic and therapeutic options are suggested including innovative molecular methods. MicroRNAs (miRNAs) are non-protein coding single stranded RNAs that regulate many cell processes. The aim of the present study is to review the deregulated miRNAs associated with PTCs. Methods: A bibliographic research was conducted, resulting in 243 articles referred to miRNAs and PTC. Regarding our exclusion criteria, 171 articles were finally included in our review. Results: A large number of miRNAs have been found to be deregulated during PTC manifestation in the literature. The deregulated miRNAs are detected in tissue samples, serum/plasma and FNA samples of patients with PTC. These miRNAs are related to several molecular pathways, involving genes and proteins responsible for important biological processes. MiRNA deregulation is associated with tumor aggressiveness, including larger tumor size, multifocality, extrathyroidal extension, lymphovascular invasion, lymph node and distant metastasis and advanced TNM stage. Conclusion: MiRNAs are proposed as new diagnostic and therapeutic tools regarding PTC. They could be essential biomarkers for PTC diagnosis applied in serum and FNA samples, while their contribution to prognosis is of great importance.